Ultrasonographic findings of intrahepatic lymphoepithelioma-like cholangiocarcinoma associated with Epstein–Barr virus: Two cases report. Issue 3 (January 2019) - Ling, Wenwu; Lu, Changli; Huang, He; Qiu, Tingting; Lu, Qiang; Huang, Chengwu; Gong, Ping; Luo, Yan; Chen, Shigao
Abstract: Rationale: Epstein–Barr virus (EBV)-related lymphoepithelioma-like cholangiocarcinoma (LELCC) is an extremely rare primary liver tumor with nonspecific clinical manifestations. The clinicopathological features of EBV-associated LELCC have been reported in a few cases. But reports of the tumor's imaging characteristics, particularly ultrasonographic findings, are very rare. Patient concerns: The first patient was a 64-year-old man with left upper quadrant pain and no nausea and dizziness for about 3 months. The second patient was a 40-year-old man, had an incidental finding of a hepatic tumor in a routine health checkup at a local hospital. Diagnoses: In the first patient, the abdominal ultrasound demonstrated a slightly heterogeneous hypoechoic nodule in segment 3 of the liver. The nodule was about 2.0 cm × 1.7 cm in size, with a clear margin and regular shape. Color Doppler flow imaging (CDFI) revealed no blood flow signals in this nodule. According to the clinical information and imaging features, it was difficult to determine the diagnosis of the nodule. In the second patient, gray-scale ultrasound revealed a slightly heterogeneous hypoechoic mass measuring 3.5 cm × 2.5 cm with well-defined margin and regular shape at the superior segment of the left hepatic lateral lobe. There was a blurrily hypoechoic halo around the mass. In contrast-enhanced ultrasound (CEUS), the mass was homogeneous hyperenhancement in the arterial phase. In the portal phase and late phase, the center enhancement of the mass washed out gradually, presenting hypoenhancement, Therefore, the tumor was diagnosed as malignancy. Intervention: Finally, a laparoscopic left hepatic lateral lobectomy was performed in the first patient. The second patient underwent a left hepatectomy with cholecystectomy. Outcomes: The first patient has been alive without recurrence or distant metastases for 11 months since the surgery. The second patient received routine follow-up after surgery. Until now, he has been tumor-free for 32 months. Lessons: We mainly focus on the ultrasound characteristics of EBV-associated LELCC, especially its enhancement patterns on CEUS, which may provide valuable information for diagnosis of the LELCC. When a liver tumor with typical CEUS patterns of malignancy is found in middle-aged adults with EBV positive, the possibility of EBV-related LELCC should be considered.